A new species of the lizard genus Bachia (Squamata: Gymnophthalmidae) from the Cerrados of Central Brazil - Rodrigues, Miguel Trefaut; Camacho, Agustín; Nunes, Pedro Murilo Sales; Recoder, Renato Sousa; Teixeira Jr., Mauro; Valdujo, Paula H.; Ghellere, José Mário B.; Mott, Tamí; Nogueira, Cristiano (Zootaxa, 2008)
A new species of Bachia of the bresslaui group, is described from Estação Ecológica Serra Geral do Tocantins, a recently created protected area in the Central Brazilian Cerrados of state of Tocantins. The new species is most similar to Bachia psamophila from which it differs in limb morphology and head and body scalation. As in Bachia psamophila the shovelshaped snout of the new species is highly prominent, an adaptation related to its psamophilous habits.